PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA PRODUK AIR MINERAL MEREK KN DI SITUBONDO - Putra, Fely Eka Yuda Hasan; Hamdun, Edy Kusnadi; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
Marketing significantly influences consumer purchases of the products or services offered for marketing success, both in product and service marketing. This study aimed to analyze and test the effect of price, product quality, purchasing decisions and consumer satisfaction. The population in the study was KN brand water products in Situbondo. The sampling technique was determined by purposive sampling. This study's data analysis and hypothesis testing used Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of testing the direct effect hypothesis using the Smart PLS 3.0 application show that price has a significant positive effect on Purchasing Decisions, Product Quality has a significant positive effect on Purchasing Decisions, Price has a positive but insignificant effect on Customer Satisfaction, Product quality has a positive but insignificant effect on Customer satisfaction, Decision has a significant positive effect on Customer satisfaction. The results of testing the hypothesis of indirect influence show that the variable price on customer satisfaction through purchasing decisions has a significant positive effect, and product quality on customer satisfaction through purchasing decisions has a significant positive effect.